KERAGAAN PERTUMBUHAN DAN KERAGAMAN GENETIK ACACIA MANGIUM WILLD. UMUR 7 TAHUN HASIL IRADIASI SINAR GAMMA (GENERASI M1) Growth Performance and Genetic Diversity of 7 Years Old Gamma Iradiated Acacia mangium Willd. (M1 Generations) - Eka Perdanawati Yunus; Supriyanto .; Iskandar Z. Siregar; Soekisman Tjirosemito; Imam Mawardi (Jurnal Silvikultur Tropika, 2017)
Mutation breeding is a powerful tool to provide novel trait in plants. However their applications in forestry are still limited. Acacia mangium is a major commercial plantation species in Indonesia and other Southeast Asia countries. Therefore, we were trying to improve its productivity. In 2008, 1200 A. mangium seeds had been irradiated by gamma ray 137Cs. There were 98 trees of M1 generations of 7 years old plantations that survive. Most of them are sterile with high clear bole and natural pruning, small branch with good growth angle,and almost straight cylindrical stem form. Based on growth performance, there were at least 29 M1 superior trees. During the observations, unexpected diversity in the bark colours with high and positive correlation to growth performance were discovered. Using microsatellite markers, the use of irradiations techniques provide surplus of heterozygosity with high value of Shannon’s Information Index. Dendrogram showed that almost all of M1 generation formed separate cluster from M0 generation with 0.71 genetic distance .Key words: mutation breeding, Acacia mangium, microsatellite